KELURAHAN UBUD DI AMBANG KEMACETAN TOTAL - Pramudya, Wisnu; Arida, I Nyoman Sukma (JURNAL DESTINASI PARIWISATA; Vol 4 No 2 (2016): VOL 4, NO 2 (2016): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2016.v04.i02.p13, 2016)
Traffic congestion in the distric of Ubud is an urgent problem. It is a logical consequence of the unpreparedness of Ubud in the face of rapid development of tourism. Construction of facilities and infrastructure provided for tourists, continuously carried out without analyzing the carrying capacity of Ubud as a tourism destination. The failure of governement authorities in managing public space in Ubud led to the emergence of traffic congestion. The purpose of this research is to find out the cause of traffic congestion as well as the action is being pursued by local community in solving traffic congestion. In this research, there are quantitative and qualitative data derived from primary and secondary data. The techniques to collect data were using observation, in-depth interview and literature study. Informants were determined by choosing the first informant, followed by key informants. The data obtained was analyzed using qualitative method and explained descriptively. Research shows the factors causing traffic congestion in the distiric of Ubud are emerged directly by two categories, internal and external categories. Local community managed to solve congestion with the realization of two central parkings, shuttle bus, traffic management and revitalization of pedestrian and traffic signs.Without real action from local government, local community have tried to solve traffic congestion with their own resources and ideas.
Keywords: traffic congestion, local community.